Relationship between adverse events prevalence, patient safety culture and patient safety perception in a single sample of patients: a cross-sectional and correlational study - Chirinos Muñoz, Mónica Susana; Orrego, Carola; Montoya, Cesar; Sunol, Rosa (BMJ open, 2023)
ObjectiveTo assess the relationship between adverse events prevalence (AEP), patient safety culture (PSC) and patient safety perception (PSP).DesignCross-sectional, ex post facto comparative study on a single sample of patients.SettingFour medium-high-level hospitals were included in the study—two public and two private from Zulia State in Venezuela.Participants556 medical records and patients were studied for the prevalence and PSP study, and 397 of the healthcare providers involved in the care of these patients were surveyed for the PSC study, at two public and two private hospitals.Outcome measurementThe primary outcome of this study was the association between AEP, PSC and PSP, and according to hospital funding type, private and public.ResultsAn inverse association was observed between AEP and its severity and Patient Safety Culture Index (rho=−0.8, p=0.5) (95% CI 0.26–0.10) and Patient Safety Perception Index (rho=−0.6, p=0.18) (95% CI 0.10–0.28), which were protective factors for patient safety. No association was identified between PSC and PSP (rho=0.0001). No statistical differences were identified by hospital type (p=0.93) (95% CI 0.70–1.2).ConclusionsThe analysis of the variable correlations studied (AEP, PSC and PSP) within the same sample offers an interesting and useful perspective. In this sample, although no correlation was observed between the three variables as an interacting set, some correlation patterns were observed between pairs of variables that could guide further studies.